Pengembangan E-Modul Ekonomi Menggunakan Aplikasi Flip-Pdf - Annisa Afra Dhia; Friyatmi Friyatmi (Jurnal Salingka Nagari, 2024)
This study aimed to develop a valid and practical e-modules using Flip-PDF Professional for economics lessons in high school. It was research and development that employed a 4D model which included stages of defining, designing, developing, and disseminating. Data were collected using validation instruments and questionnaires given to students and teachers. Descriptive statistics with mean and percentage were used to analyze the data. The results show that the e-module is valid for economics learning and it is highly practical for economics learning, with teachers rating 84 percent and students rating 92.24 percent.